Prosody as a component of sense - Grzegorzewska, Anita (2021)
The researching of the mechanisms that rule the sense composing, in process of receiving the communique, is still of interest to researchers – Aleksy Awdiejew and Grażyna Habrajska – the creators of Polish communicativism theory. However, there were no deliberations dedicated to prosody. The purpose of presented publication is to refill this vacancy.  Author, referring to the theoretical basics of commucativism, researches the process of communicating the sense, using suprasegmental elements of speech (stress and intonation) and segmental elements (pause). She offers an auditory analysis of material extracted from 16 different audiobooks of literature classics. The proprietary system of prosodic elements’ notation allows to observe and to record the acoustic value of the communiques. Using this system isn’t a purpose itself – it’s used for professional analysis of a prosodic frame.   Communicative approach of the prosody contributed to initiate a new field of study: prosody pragmatics. According to this, author describes prosody that: 1) does not interfere with interactive power of communique (prosody read); 2) can sensitize, weaken or modify this power (prosody derived or interpreted). She extracts and classifies all prosody’s characteristics within the groups of interactive operators they create; she recreates the process of supporting the sense’s composing using prosody, by comparing primary (by author of the text) and secondary (by actor reading the text) prosodic interpretation of the text. She also designates the classes of phenomena, within recipients can build some area of meaning in their own imagination.
Keywords: prosody; compositing the sense; communicativism; auditory analysis